Implementasi Pesan Tahbisan Guru Huria Dan Bimbingan Agama Kristen Oleh Keluarga Terhadap Perwujudan Jemaat Misioner Di HKBP Resort Pansurnapitu Tapanuli Utara Tahun 2020 - Benny Hutahaean; Marudut Situmorang; Luther Tarigan (Jurnal Euangelion, 2021)
Abstract: This study aims to determine the implementation of the Guru Huria HKBP ordination message to the embodiment of the missionary congregation at HKBP Pansurnapitu Resort, to know the Christian religious guidance by the Family towards the embodiment of the missioner congregation in HKBP Pansurnapitu, This research use combain qualitative and quantitative methods. The sample in this research is the HKBP resort pansurnapitu from 18 people. The research instrument was in the form of a closed questionnaire, which was arranged by the researcher based on the research variable indicators. The questionnaire trial was conducted on 50 people who were not research samples. The results of this study prove the relationship between the implementation of the Guru Huria HKBP ordination can create Missioner Congregations at HKBP Resort Pansurnapitu. On the implementation of the Guru Huria ordination variable to the missioner congregation there is a positive relationship. It is shown that the significance value of Sig. (2-tailed) between the implementation of the Guru Huria ordination and the missioner congregation is 0.003 <0.05 and rcount> rtable that is 0.826> 0.468 which means that there is a significant correlation between the implementation of the Guru Huria ordination variable with missioner congregation at HKBP resort pansurnapitu. The relationship of Christian guidance by the HKBP family can realize the missioner congregation at HKBP resort pansurnapitu there is a positive relationship seen from the Sig. (2-tailed) value of 0.001 <0.05 and rcount> rtable that is 0.799> 0.468 ,, so there is a correlation significant between Christian religious guidance by families and missioner congregations at HKBP pansurnapitu resorts. The results of the analysis of the description of the variable HKBP missioner congregation can realize the missioner congregation at HKBP resort pansurnapitu which shows the results of the analysis is very significant. Where the value of person correlation between each variable connected has two asterisks (**) so that the variable implementation of Guru Huria ordination and Christian religious guidance by families with missioner congregations is very significant at 1%. The R square value obtained is 0.736 or 73.6%. Significant value of 0.00 which means <significance criteria (0.05), thus the linear regression equation model and meet the linearity criteria. With the regression equation model Y = 3.566 + 0.095X1 + 0.793X2.